Near Infrared Photoimmunotherapy Targeting EGFR Positive Triple Negative Breast Cancer: Optimizing the Conjugate-Light Regimen. - Tadanobu Nagaya; Kazuhide Sato; Toshiko Harada; Yuko Nakamura; Peter L Choyke; Hisataka Kobayashi (PLoS ONE)
Aim Triple-negative breast cancer (TNBC) is considered one of the most aggressive subtypes of breast cancer. Near infrared photoimmunotherapy (NIR-PIT) is a cancer treatment that employs an antibody-photosensitizer conjugate (APC) followed by exposure of NIR light for activating selective cytotoxicity on targeted cancer cells and may have application to TNBC. In order to minimize the dose of APC while maximizing the therapeutic effects, dosing of the APC and NIR light need to be optimized. In this study, we investigate in vitro and in vivo efficacy of cetuximab (cet)-IR700 NIR-PIT on two breast cancer models MDAMB231 (TNBC, EGFR moderate) and MDAMB468 (TNBC, EGFR high) cell lines, and demonstrate a method to optimize the dosing APC and NIR light. Method After validating in vitro cell-specific cytotoxicity, NIR-PIT therapeutic effects were investigated in mouse models using cell lines derived from TNBC tumors. Tumor-bearing mice were separated into 4 groups for the following treatments: (1) no treatment (control); (2) 300 μg of cet-IR700 i.v., (APC i.v. only); (3) NIR light exposure only, NIR light was administered at 50 J/cm2 on day 1 and 100 J/cm2 on day 2 (NIR light only); (4) 300 μg of cet-IR700 i.v., NIR light was administered at 50 J/cm2 on day 1 after injection and 100 J/cm2 of light on day 2 after injection (one shot NIR-PIT). To compare different treatment regimens with a fixed dose of APC, we added the following treatments (5) 100 μg of cet-IR700 i.v., NIR light administered at 50 J/cm2 on day 1 and 50 μg of cet-IR700 i.v. immediately after NIR-PIT, then NIR light was administered at 100 J/cm2 on day 2, which were performed two times every week ("two split" NIR-PIT) and (6) 100 μg of cet-IR700 i.v., NIR light was administered at 50 J/cm2 on day 1 and 100 J/cm2 on day 2, which were performed three times per week ("three split" NIR-PIT). Result Both specific binding and NIR-PIT effects were greater with MDAMB468 than MDAMB231 cells in vitro. Tumor accumulation of cet-IR700 in MDAMB468 tumors was significantly higher (p < 0.05) than in MDAMB231 tumors in vivo. Tumor growth and survival of MDAMB231 tumor bearing mice was significantly lower in the NIR-PIT treatment group (p < 0.05). In MDAMB468 bearing mice, tumor growth and survival was significantly improved in the NIR-PIT treatment groups in all treatment regimens (one shot NIR-PIT; p < 0.05, "two split" NIR-PIT; p < 0.01, "three split" NIR-PIT; p < 0.001) compared with control groups. Conclusion NIR-PIT for TNBC was effective regardless of expression of EGFR, however, greater cell killing was shown with higher EGFR expression tumor in vitro. In all treatment regimens, NIR-PIT suppressed tumor growth, resulting in significantly prolonged survival that further improved by splitting the APC dose and using repeated light exposures.